Combined predictive value of triglyceride-glucose index and remnant cholesterol for coronary artery disease in young adults - Wu, Xi; Wu, Mingxing; Huang, Haobo; Liu, Zhe; Huang, He; Wang, Lei (Frontiers in Cardiovascular Medicine, 2025)
IntroductionCoronary artery disease (CAD) is increasingly prevalent in individuals aged ≤45 years, yet effective early detection strategies remain lacking. Insulin resistance (IR) and remnant cholesterol (RC) burden are critical contributors to early atherosclerosis, highlighting the potential utility of novel markers such as the triglyceride-glucose (TyG) index and RC.MethodsIn this retrospective study, we analyzed 458 patients aged ≤45 years who underwent coronary angiography (CAG). The TyG index and RC were calculated using standard fasting plasma glucose (FPG) and lipid profiles. Participants were classified into normal coronary, CAD, single-vessel disease (SVD), and multi-vessel disease (MVD) groups. Logistic regression analysis was performed to identify independent predictors of CAD and MVD. Receiver operating characteristic (ROC) curves were used to evaluate the discriminative ability of TyG and RC.ResultsBoth the TyG index and RC were significantly higher in patients with CAD compared with controls (P < 0.001), and further elevated in those with MVD. In multivariate analysis, TyG (odds ratio [OR] = 1.393) and RC (OR = 1.475) were independently associated with CAD and also predicted MVD (TyG OR = 2.363; RC OR = 3.692). RC had a higher area under the curve (AUC) for identifying CAD than TyG (0.773 vs. 0.669), whereas TyG had greater predictive value for MVD (AUC = 0.775 vs. 0.683).DiscussionThe TyG index and RC are independent, complementary, and accessible biomarkers for assessing early CAD risk in young adults. RC showed higher sensitivity in identifying the presence of CAD, while higher TyG index values were associated with multi-vessel involvement. Incorporating these markers into screening protocols may enhance early risk stratification and help prevent premature atherosclerosis in young populations.